ΔNp63 Is Essential for Epidermal Commitment of Embryonic Stem Cells - Medawar, Alain (Public Library of Science, 2008)
In vivo studies have demonstrated that p63 plays complex and pivotal roles in pluristratified squamous epithelial development, but its precise function and the nature of the isoform involved remain controversial. Here, we investigate the role of p63 in epithelial differentiation, using an in vitro ES cell model that mimics the early embryonic steps of epidermal development. We show that the ΔNp63 isoform is activated soon after treatment with BMP-4, a morphogen required to commit differentiating ES cells from a neuroectodermal to an ectodermal cell fate. ΔNp63 gene expression remains high during epithelial development. P63 loss of function drastically prevents ectodermal cells to commit to the K5/K14-positive stratified epithelial pathway while gain of function experiments show that ΔNp63 allows this commitment. Interestingly, other epithelial cell fates are not affected, allowing the production of K5/K18-positive epithelial cells. Therefore, our results demonstrate that ΔNp63 may be dispensable for some epithelial differentiation, but is necessary for the commitment of ES cells into K5/K14-positive squamous stratified epithelial cells.